Dhikr Therapy: Overcoming Life Anxiety with Islamic Counseling Based on QS Ar-Ra'd Verse 28 - Indriani, Tiya; Jarkawi, Jarkawi; Ridhani, Akhmad Rizkhi (Al-Hayat: Journal of Islamic Education, 2024)
This research aims to conduct a literature review regarding the effectiveness of dhikr-based Islamic counseling in overcoming life anxiety based on the Al-Qur'an Surah Ar-Ra'd verse 28. The literature research method applied is statements and checklists, using the "Preferred Reporting Items" approach. for Systematic Reviews and Meta-Analysis" (PRISMA). Data and data sources were obtained through a literature search for articles from Google Scholar. The data collection technique is carried out by selecting studies that meet the specified criteria. Data analysis was carried out by utilizing keywords such as "Q.S. Ar-Ra'd verse 28", "Life Anxiety", and "Stages of Individual Counseling". The results of the research show that Islamic counseling which integrates dhikr based on verse 28 of Surah Ar-Ra'd is able to provide calm, peace and tranquility in the heart as a soother for the soul. Individual counseling stages that use the dhikr words Istigfar, Tasbih, Tahmid, Takbir, Tahlil, and Asmaul Husna can generally be applied in Islamic counseling, with the possibility of applying dhikr bi al nafs. This research develops the concept of Islamic counseling by exploring Islamic values contained in verse 28 of Surah Ar-Ra'd, aiming to reduce life anxiety in each individual.